2012
DOI: 10.1016/j.jaac.2012.04.010
|View full text |Cite|
|
Sign up to set email alerts
|

Examining Autism Spectrum Disorders by Biomarkers: Example From the Oxytocin and Serotonin Systems

Abstract: Objective Autism Spectrum Disorder (ASD) is a heritable but highly heterogeneous neuropsychiatric syndrome, which poses challenges for research relying solely on behavioral symptoms or diagnosis. Examining biomarkers may give us ways to identify individuals who demonstrate specific developmental trajectories and etiological factors related to ASD. Plasma oxytocin (OT) and whole blood serotonin (5-HT) levels are consistently altered in some individuals with ASD. Reciprocal relationships have been described betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 102 publications
2
65
2
2
Order By: Relevance
“…Although some researchers regarded 5-HT (Hammock et al, 2012) and cytokines (Abdallah et al, 2013) as a potential biomarker for autism, only association analysis was used in most of studies. However, it is not sufficient to define the biomarker only by correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although some researchers regarded 5-HT (Hammock et al, 2012) and cytokines (Abdallah et al, 2013) as a potential biomarker for autism, only association analysis was used in most of studies. However, it is not sufficient to define the biomarker only by correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that children with autism showed lower plasma OT levels [10,11] than children without autism. Our findings are in line with these previous studies, as autistic traits include persistency.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have investigated the association between social behavior and circulating OT levels among children with autism spectrum disorders [10,11] or schizophrenia [12]. Further, several studies reported the effectiveness of intranasal application of OT to improve social behavior among autism spectrum disorders or schizophrenia, in which social behavior is a central role [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human blood of ITGB3 genotyped subjects was collected under an approved institutional review board protocol (the University of Illinois at Chicago) (Hammock et al, 2012). All subjects provided informed consent for research studies.…”
Section: Western Blot Of Human Platelet Samplesmentioning
confidence: 99%